Interplay Between the Immune and Endocrine Systems in the Lung: Implications for TB Susceptibility - Webber, Tariq; Ronacher, Katharina; Conradie-Smit, Marli; Kleynhans, Léanie (Frontiers in Immunology, 2022)
The role of the endocrine system on the immune response, especially in the lung, remains poorly understood. Hormones play a crucial role in the development, homeostasis, metabolism, and response to the environment of cells and tissues. Major infectious and metabolic diseases, such as tuberculosis and diabetes, continue to converge, necessitating the development of a clearer understanding of the immune and endocrine interactions that occur in the lung. Research in bacterial respiratory infections is at a critical point, where the limitations in identifying and developing antibiotics is becoming more profound. Hormone receptors on alveolar and immune cells may provide a plethora of targets for host-directed therapy. This review discusses the interactions between the immune and endocrine systems in the lung. We describe hormone receptors currently identified in the lungs, focusing on the effect hormones have on the pulmonary immune response. Altered endocrine responses in the lung affect the balance between pro- and anti-inflammatory immune responses and play a role in the response to infection in the lung. While some hormones, such as leptin, resistin and lipocalin-2 promote pro-inflammatory responses and immune cell infiltration, others including adiponectin and ghrelin reduce inflammation and promote anti-inflammatory cell responses. Furthermore, type 2 diabetes as a major endocrine disease presents with altered immune responses leading to susceptibility to lung infections, such as tuberculosis. A better understanding of these interactions will expand our knowledge of the mechanisms at play in susceptibility to infectious diseases and may reveal opportunities for the development of host-directed therapies.